Evaluación de las variables del comportamiento organizacional mediante la instrumentación de gestión por procesos en la microempresa quesería alimentos frescos. - Zambrano Macías, Detsy Patricia (2017)
The present research was carried out at the Quesería Alimentos Frescos microenterprise located in the San Isidro parish belonging to the canton Sucre in the province of Manabí, it had as objective was to evaluate of the variables of the organizational behavior through the implementation of the management by processes, therefor an organized structure was made where techniques (interviews, surveys and observation) and methods (inductive, deductive, descriptive, bibliographic, field and Delphi) were used, which allowed establishing the guidelines for structuring a proposal for an improvement program that optimized the compliance with the variables of Organizational Behavior in the context of the processes studied through the application of the matrix tool 5W + 1H. The investigative work allowed to obtain a different vision with the relation to the perception that had the managers of the microenterprise that evidenced the level of fulfillment in which the studied variables were found, the results of the study provide the tools for the change in management behavioral improvement of workers.